The influence of pacing strategy on VO2 and supramaximal kayak performance - Bishop, D.; Bonetti, D.; Dawson, B. (Medicine & Science in Sports & Exercise, 2002)
PURPOSE: The purpose of this study was to investigate the effects of manipulating pacing strategy on VO2 and kayak ergometer performance in well-trained paddlers. METHODS: Eight well-trained kayak paddlers (500-m time = 115-125 s) first performed a graded exercise test for determination of VO2max and lactate (La-) parameters. On subsequent days and in a random, counterbalanced order, subjects performed a 2-min, kayak ergometer test using either an all-out start or even pacing strategy. RESULTS: There was a significantly greater peak power (747.6 +/- 152.0 vs 558.3 +/- 110.1 W) and average power (348.5 +/- 47.6 vs 335.5 +/- 44.8 W) using the all-out start strategy, when compared with the even-paced strategy. There was however, no significant difference between the two pacing strategies for peak VO2, accumulated oxygen deficit (AOD), peak [La-], or posttest pH. Using the all-out start, total VO2 was significantly greater (7.3 +/- 0.8 vs 6.9 +/- 0.8 L). CONCLUSION: The results of this study indicate that 2-min kayak ergometer performance is significantly greater following an all-out start strategy when compared with an even-paced strategy. The improved performance appears to be attributable to faster VO2 kinetics, without a significant change in the total AOD (although the AOD distribution was altered).